2002
DOI: 10.1080/1357714021000022168
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment and Outcome of Patients With Soft Tissue Sarcomas and Synchronous Metastases

Abstract: Most primary tumors were >/=10 cm (58%), high-grade histology (77%), and located on the extremity (60%).The most frequent site of metastatic disease was the lung (63%); 27% of patients had metastases to >/=2 organ sites. Surgery to the primary tumor was performed in 94% of patients (n = 45) and 68% had additional radiation therapy (n = 32). Thirty- five percent of patients underwent at least one metastastectomy (n = 17). Chemotherapy was administered to 90% of patients (n = 43); 31% received >/=3 different reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 19 publications
(17 reference statements)
2
26
0
Order By: Relevance
“…Of all patients diagnosed with malignant musculoskeletal tumors, 5-30% (1-3) have a recurrence and 10-38% of patients present with clinically detectable metastases (4)(5)(6). A number of studies have reported the survival of patients who have undergone either a lung metastasectomy or chemotherapy (4,5,(7)(8)(9).However, little is known about the clinical course of patients with bone or soft tissue sarcomas who have succumbed to the disease. For example, only a few reports are available regarding the clinical course, such as the metastatic site, which led to the cause of death or the survival time following initial detection of metastases (10).…”
Section: Introductionmentioning
confidence: 99%
“…Of all patients diagnosed with malignant musculoskeletal tumors, 5-30% (1-3) have a recurrence and 10-38% of patients present with clinically detectable metastases (4)(5)(6). A number of studies have reported the survival of patients who have undergone either a lung metastasectomy or chemotherapy (4,5,(7)(8)(9).However, little is known about the clinical course of patients with bone or soft tissue sarcomas who have succumbed to the disease. For example, only a few reports are available regarding the clinical course, such as the metastatic site, which led to the cause of death or the survival time following initial detection of metastases (10).…”
Section: Introductionmentioning
confidence: 99%
“…From 5% to 30% of patients with STS have a local recurrence, and from 10% to 38% present with clinically detectable metastases 2, 3, 4, 5. The development of new systemic treatments for patients with STS has been limited in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Other treatment options include radiotherapy and chemotherapy, which can be combined with surgical techniques for larger lesions, since large tumors (>5 cm in diameter) respond poorly to nonsurgical treatment. 1,2 In humans with metastatic disease, chemotherapy produces poor response rates of 20%, which does not have an impact on overall survival. 1,2 Overall, five year survival rate is approximately 35-65%, with size of the tumor being the most important prognostic factor.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In humans with metastatic disease, chemotherapy produces poor response rates of 20%, which does not have an impact on overall survival. 1,2 Overall, five year survival rate is approximately 35-65%, with size of the tumor being the most important prognostic factor. 1,3 Due to a poor response rate and limited treatment options, newer therapeutic approaches are considered, either as primary or adjuvant therapy to conventional methods in order to improve the clinical outcome of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%